(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The recent outbreak of deadly virus called COVID-19 has posed serious challenges to the whole world, be it to cure or prevent its further spread or to survive with it or to revive the economy from its impact. With no vaccine at present to prevent the deadly virus, the imposition of travel restriction and stay at home orders has caused severe impact on various socio-economic dimensions especially tourism sector. In view of preventing the spread of virus the government of India has imposed a nationwide lockdown which leads to complete stop on travel and tourism. The global or interstate travel has been restricted, people were not allowed to visit any place and almost all the business sectors had to close except the daily or basic needs. This gave a huge shock and setback to the economy of Nation. Ladakh which got the status of Union Territory after the abrogation of Article 370 on 5 August 2019 is not an exception in this crisis and its economy had suffered a lot as the region’s major economic contribution depends on tourism and its hospitality sector. The present work aims to identify, investigate and analyse the impact of COVID-19 on the tourism sector of Ladakh. The present study is based on secondary sources of data which has been obtained from various organisations such as Department of Tourism Jammu and Kashmir, Ministry of Tourism Government of India and Economic Survey of Jammu and Kashmir, various research articles news papers, etc. in order to gain fruitful results. Furthermore, the chapter also puts forth various suggestions and recommendations for the revival and sustainable tourism development in the region.